KEPATUHAN MINUM OBAT PADA PASIEN HIV/AIDS DITINJAU DARI INTERAKSI PROFESIONAL KESEHATAN DI PUSKESMAS PESANTREN 1 KEDIRI - Dyah Ayu Kartika Wulan Sari; Vitaria Wahyu Astuti; Erva Elli Kristanti; Maria Anita Yusiana (Jurnal Keperawatan Malang, 2024)
Background : HIV/AIDS patients require ongoing treatment but the compliance is still low. Non-compliance for taking medication can cause resistance in patients with HIV/AIDS Purpose: The aim of this research is to analyze the relationship between health worker interactions and medication adherence at HIV/AIDS patient Methods: The design of this research is cross sectional. The population is patients with HIV/AIDS at Pesantren 1 Kediri Health Center. The research sample was 66 people using consecutive sampling. Data collection uses a questionnaire. Measurement of patient adherence levels based on the Follow-up Overview of HIV Patient Care and Antiretroviral Therapy at the Pesantren 1 Kediri Health Center. Data analysis used was the Spearman Rho test Result: The research results showed that the Health Professional Interaction of HIV/AIDS patients at Pesantren 1 Kediri Health Center had a Health Professional Interaction with a Positive score of 64 respondents (97.0%). Compliance of taking medication by HIV/AIDS patients obtained level 1 compliance of more than 50% for 40 respondents (60.6%) and the results of the Spearman Rho test were ρ=0.254, which means that there was no correlation between the two variables. Implication:In conclusion, there is no relationship between health workers interaction and medication adherence in HIV/AIDS patients. The findings of this study, further research is expected to explore other factors related to medication adherence in HIV/AIDS patients, so hopefully can obtain the best solution to increase patient medication adherence, especially in HIV-AIDS patients.